Surgical versus conservative treatment of odontoid fractures in the elderly: A randomized controlled clinical study (SCORE) - Arthur Wagner; Carolin Albrecht; Sophie Dittmer; Silvia Egert-Schwender; Victoria Kehl; Rita Stichling; Gisela Klatt; Barbara Ettinger; Nils Hecht; Peter Vajkoczy; Alexander Wengert; Frank Kandziora; et al. (PLoS ONE, 2025)
Background Odontoid fractures of the second cervical vertebra commonly affect elderly patients due to osteoporosis and low-energy trauma. Treatment is controversial, with prolonged cervical collar immobilization risking non-union and complications, and surgical C1–C2 stabilization involving higher upfront surgical risks. High-level evidence from randomized controlled trials to guide optimal treatment decisions is lacking. The SCORE study aims to determine whether surgical stabilization is non-inferior to conservative collar management in maintaining functional independence for elderly patients with unstable odontoid fractures. Methods SCORE is a multicenter, parallel-group, randomized controlled non-inferiority trial enrolling 322 patients aged ≥70 years with acute (≤2 weeks) unstable odontoid Type II, III, or atypical fractures. Participants will be randomized 1:1, stratified by center, to receive surgical stabilization via posterior C1–C2 fixation or conservative management with a rigid cervical collar. The primary outcome measure is the change in Barthel Index (BI) from baseline to 12 weeks. Secondary outcomes include quality of life (EQ-5D), neck pain (Visual Analog Scale, VAS), neck disability (Neck Disability Index, NDI), radiographic fusion, treatment compliance, cross-over rates to surgery, and incidence of adverse and serious adverse events up to 6 months. Follow-ups will take place at 12 weeks and 6 months post-injury, with an additional visit at approximately 2 weeks post-surgery for surgical patients. Analysis will use mixed models for repeated measures, targeting 90% power to detect non-inferiority within a 5-point margin on the BI (one-sided α = 0.025), accounting for 15% attrition. Discussion This trial addresses a critical evidence gap by directly comparing surgical and conservative treatments, aiming to guide clinical decision-making and improve functional outcomes and quality of life in elderly patients. Trial registration ClinicalTrials.gov, ID: NCT06961578